Relación entre el uso del chat y los juegos en red en las habilidades sociales de los alumnos de primer y segundo año de Ingeniera de Sistemas y Psicología de la Universidad Peruana Unión - Vilca Quiro, Lindsey Wildman (2019)
Objective: To determinate the relate that exist between the use of chat and online games on social skills of studentsin first and second years of Systems Engineering and Psychology. Methods: We used a nonrandom sample of convenience sample of university students from the Universidad Peruana Unión of Lima, including college students ofboth sexes aged between 15 and 25. Results: The results indicate that students in the Engineering Systems (50%) aregenerally characterized by moderate use of chat. On the other hand, we observe that psychology (50%) comparedto systems engineering (16.3%) used very little chat. As for gaming, Psychology (96.4%) is characterized by verylittle play online games like the Systems Engineering degree (63.8%). Although the Engineering Systems (30%)had a level of average usage of online gaming, and with respect to social skills have to Psychology course (97.6%)were characterized by a high level of social skills. Similarly also applies to the Engineering Systems (91.3%). Conclusions: Therefore the correlation ratio indicates that there is a highly significant negative relationship between theuse of chat and social skills (r = - 0.419, p <0.01). This means that the lower the level of use of chat higher the levelof social skills. There is also a highly significant negative relationship between the use of online games and socialskills (r = - 0.215, p <0.01). This means that the greater use of smaller online games are social skills.